PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI MIE GACOAN MAGELANG - Kusumawardani, Berlian Hema; Achsa, Andhatu (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
The purpose of the research is to ascertain how product and service quality affects customers' satisfaction when they purchase meals at Mie Gacoan Magelang. The research employs primary data, such as the distribution of questionnaires and the purpose side as a sampling strategy from at least 60 respondents, or the residents of Magelang, to acquire data from the area where it is done. The suggested research methodology is a quantitative one. When managing its own data using SPSS as a method of analysis, testing the instrument utilizes the forms of validity test, reliability test, classical acceptance test, multiple linear regression equation analysis, t-test, F-test, and test of the coefficient of determination. The data processing analysis results show that Y = 0.865 + 0.270 x 1 + 0.308 x 2 + e, and the fitted R-squared is 0.722, which means that product quality and service quality contribute 72% to consumer satisfaction, with the remaining 38% being the result of other influences that were not taken into consideration.